Considering musical structure in location-based experiences - Hazzard, Adrian; Benford, Steve; Chamberlain, Alan; Greenhalgh, Chris (2015)
Locative music experiences are often non-linear and as such the final structure of the music heard is guided by the movements of the user. We note an absence of principles regarding how composers should approach the structuring of such locative soundtracks. For instance, how does one compose for a non-linear soundtrack using linear, pre-composed placed sounds, where fixed musical time is placed into the indeterminate time of the user’s experience? Furthermore, how does one create a soundtrack that is suitable for the location, but also functions as a coherent musical structure? We explore these questions by analyzing an existing ‘placed sound’ work from a traditional music theory perspective and in doing so reveal some structural principals from ‘fixed’ musical forms can also support the composition of contemporary locative music experiences.